PENETAPAN GANTI KERUGIAN TERHADAP PELEPASAN HAK GUNA USAHA PT. PERKEBUNAN NUSANTARA II UNTUK PEMBANGUNAN JALAN TOL MEDAN-BINJAI - MUHAMMAD RIZKI SYAHPUTRA (PREMISE LAW JURNAL, 2017)
In order to increase road service, the road organizer needs to improve road network system by improving road condition and constructing toll roads. The Medan-Binjai toll road which has been planned by the government passes plantation area of PTPN (PT Perkebunan Nusantara) II. Therefore, it is necessary to coordinate with the party concerned about land clearing and about compensation on the land and asset of PTPN II which have the impact of the toll road construction. The research problems were as follows: how about the implementation of the renunciation of rights of the leasehold land of PTPN II for the Medan-Binjai toll road construction, how about the compensation of the land acquisition for the Medan-Binjai toll road construction, and how about legal protection for PTPN II in the renunciation of rights for the Medan-Binjai toll road construction. Keywords: Transfer of Title, Land Acquisition, Toll Road Construction